Multi-system sustainability transitions in developing countries : a case study of the electric car in Brazil - Coutinho, Gabriel Leuzinger (2023)
Tese (doutorado) — Universidade de Brasília, Centro de Desenvolvimento Sustentável, Programa de Pós-Graduação em Desenvolvimento Sustentável, 2023.